Separation of xylose from glucose in oil palm frond (OPF) bagasse hydrolysate using nanofiltration membrane system - Nurul Fatihah, Mahamad Roli (2018)
Separation of biomass hydrolysate that contain glucose and xylose was done in a cross-flow system, using a commercial spiral wound nanofiltration (NF) membrane with molecular weight cut off (MWCO) ranging from 150 to 1000 g/mol. Xylose is an intermediate product in xylitol production and glucose interferes in the process of separation. The molecular weight of glucose is 1.2 times higher than the molecular weight of xylose. These two different types of monosaccharides can possibly be separated using NF membrane according to their molecular size rather than diffusivities. Thus the aim of this study are to develop and evaluate the performance of pilot scale commercial spiral wound NF membrane namely Desal-5 DK, Desal-5 DL and NF90 for separation of xylose from glucose. The feedstock used was biomass from oil palm frond (OPF) bagasse. The separation of sugar was started using xylose-glucose model solution before run with OPF hydrolysate. The filtration was operated in total recycled mode at 5 to 10 bar. The sugar concentration was analyzed using high performance liquid chromatography (HPLC). From this study, Desal-5 DK membrane gave the higher xylose separation factor at 1.17 as compare to Desal-5 DL (0.81) and NF90 membranes (0.84) when using model solution. There are several operating parameter used to evaluate the performance of membrane, which are transmembrane pressure (TMP), total feed concentration (C0) and ratio xylose to glucose. The crossflow effect from the operating parameter was tested using binary model solution. Xylose and glucose rejection are dependent on the effective filtration pressure. According to the result in this study, glucose rejection is up to 90 % and xylose rejections up to 80 % when pressure increased. Maximum separation factor 2.47 was achieved when xylose concentration ratio was 3.2 % in total feed concentration with 10 % of glucose. This is due to higher concentration of larger molecule (glucose) pushes smaller molecule (xylose) through the membrane, enhancing xylose permeation. Meanwhile, equal ratio of xylose to glucose (50:50) at high feed concentration, 10 % promoted to high separation factor which is 2.16. The separation of OPF hydrolysate in this present work gave low rejection of xylose between 10 to 30 %. This is due to low pressure at 5 to 10 bar was applied during the separation. The xylose separation factor was up to 1.63 when increased in feed pressure while inhibitors present in OPF bagasse hydrolysate are retained more due its lower separation factor. The inhibitors most probably cannot pass through the membrane due to xylose molecule size was bigger and block them. Overall, it can be concluded that the spiral wound nanofiltration membrane offers cost-effective and easy-maintenance, which has a potential in xylose-glucose separation.